(untitled) (European Journal of Economics, Finance and Business Development, 2025)
Modern. economy under the circumstances every one company for every how method and tools through done increaseable financial - economic activity efficiency constant monitoring important importance has. Analytical point of view from the point of view such monitoring efficiency analysis certain method how correct selected and to be used related. Organization efficiency how much high if , external and internal users for necessary the information that is inside received effective information the company financial status and management different at the levels acceptance made of decisions efficiency so much reliable It will be.